2021
DOI: 10.3389/fmicb.2021.662783
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic Investigation Uncovers Presence of Probiotic-Type Microbiome in Kalparasa® (Fresh Unfermented Coconut Inflorescence Sap)

Abstract: The phloem sap tapped from unopened inflorescence (spadix) of coconut palm using a novel collecting device, “coco-sap chiller,” has been branded Kalparasa® (henceforth as Kalparasa in the text) to distinguish its properties not found in sap harvested by traditional methods. To know its hitherto unidentified microbiome profile, we employed high-throughput sequencing to uncover the bacteriome and mycobiome in fresh and 12-h fermented samples. Fresh Kalparasa had a pH of 7.2, which dropped to 4.5 after 12 h, sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…Te decrease in pH is often a result of the accumulation of specifc acids, such as lactic acid or acetic acid, depending on the microorganisms involved in the fermentation process [12]. Gopal et al [20] reported that the fermentation of neera due to the symbiotic culture of bacteria and yeasts. Te titratable acidity increased from 0.024% to 0.367%.…”
Section: Resultsmentioning
confidence: 99%
“…Te decrease in pH is often a result of the accumulation of specifc acids, such as lactic acid or acetic acid, depending on the microorganisms involved in the fermentation process [12]. Gopal et al [20] reported that the fermentation of neera due to the symbiotic culture of bacteria and yeasts. Te titratable acidity increased from 0.024% to 0.367%.…”
Section: Resultsmentioning
confidence: 99%
“…In the current study, the best response value or pH value of the coconut sap was determined to be the largest, which indicates that the microorganisms in coconut sap have not yet undergone fermentation, and the sugar has been not degraded [ 30 , 31 ]. These findings align with the preliminary results obtained in the study.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, there were two unique favorable floras present in Ferment: Gluconobacter and Lactobacillus. Gluconobacter is found as a probiotic in fresh unfermented coconut juice ( Gopal et al, 2021 ) and is considered a health-associated probiotic in fermented food ( Leech et al, 2020 ). Studies have reported that Lactobacillus acidophilus gavage reduced the levels of pro-inflammatory cytokines, promoted the increase of goblet cells and the secretion of antimicrobial peptides, regulated the ratio of Firmicutes / Bacteroidetes , and increased the level of acetate ( Wang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%